1980
DOI: 10.4141/cjas80-114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biotin Supplementation on Reproductive Performance and Foot Lesions in Swine

Abstract: reproductive performance and foot lesions in swine' Can. J. Anim. Sci. 60: 96r-969.Two experiments, using 231 gilts and primi-parous sows of Lacombe and Yorkshire breeding, were conducted during the winter and summer months to study the effect of biotin supplementation (200 and 300 ptglkg in exps. 1 and 2) of barley-wheat-soy gestation and lactation diets on reproductive performance and incidence of foot lesions in swine. The control and supplemented groups did not significantly differ in weight change duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Brooks et al (1977), Halama (1979) and Simmins and Brooks (1983) have also reported a" reduction in the weaning to rebreeding interval with supplemental biotin. To the contrary, Penny et al (1981) and Grandhi and Strain (1980) noted no response in the weaning to estrous interval with biotin supplementation.…”
Section: R Esultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Brooks et al (1977), Halama (1979) and Simmins and Brooks (1983) have also reported a" reduction in the weaning to rebreeding interval with supplemental biotin. To the contrary, Penny et al (1981) and Grandhi and Strain (1980) noted no response in the weaning to estrous interval with biotin supplementation.…”
Section: R Esultsmentioning
confidence: 88%
“…Halama (1979) also reported a 9% improvement in conception rate when biotin was supplemented to diets of sows showing visual signs of hair loss and foot lesions. Grandhi and Strain (1980) failed to obtain a response in conception rate with biotin supplementation.…”
Section: R Esultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Estimates of available biotin requirement for the sow (pg/kg diet) ranged from 55 to 220 (CUNHA 1972), or 137 to 540 based on extrapolated chick studies (BROOKS 1978). Since biotin supplementation of diets based on cereal and soybean meal had no effect on sow reproductive performance (EASTER et al 1979;GRANDHI & STRAIN 1980;NEWMAN & ELLIOTT 1980), it was likely that the available biotin contributed only by the cereal and soybean meal components (90-150 pg/kg) might have adequately met the biotin requirements of these sows. Data from the current study suggest that sow reproductive performance was optimised when the basal diet was supplemented with 100 pg biotin/kg to provide 147 pg available biotin/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, biotin supplemented sows took fewer days to return to postweaning oestrus (BROOKS et al 1977;HALAMA 1979;PEDERSEN & UDESEN 1980;SIMMINS & BROOKS 1983;BRYANT et al 1985) and also had higher conception rates (HALAMA 1979;SIMMINS & BROOKS 1983;BRYANT et al 1985). In contrast, other reports showed that biotin supplementation had n o effect on overall reproductive performance (EASTER et al 1979;GRANDHI & STRAIN 1980;NEWMAN & ELLIOTT 1980). Sow diets in western Canada are formulated mainly from barley and wheat, ingredients low in available biotin as measured by chick growth bioassay (FRIGG 1984;MISIR & BLAIR 1984).…”
Section: Introductionmentioning
confidence: 86%